Analisis Determinan Kecurangan Pajak Berdasarkan Perspektif Fraud Hexagon dengan Moral Pajak sebagai Variabel Moderasi - Nurul Farchani Awwaliyah; Windy Aulia Aurora; Wulan Safitri; Dien Noviany Rahmatika (JOURNAL OF SHARIA ECONOMICS, 2025)
This study analyzes the determinants of tax fraud through the perspective of Fraud Hexagon with tax morality as a moderation variable, using a systematic literature review (SLR) of 51 scientific articles published in SINTA 1-5 indexed journals from 2020 to 2025. Fraud Hexagon, which consists of six main elements namely stimulus, opportunity, rationalization, capability, arrogance, and collusion, is identified as the main predictor of tax fraud, where these elements facilitate tax avoidance practices through manipulation of financial statements. Tax morality acts as a psychological moderation that can weaken the relationship between Fraud Hexagon and tax fraud, with mechanisms such as money ethics, religiosity, and trust in tax authorities. The findings show that stimulus and opportunity are the most dominant elements in encouraging tax evasion, while high tax morale can intervene in these risks through increased voluntary compliance. Practical implications include policy recommendations to strengthen oversight of the tax system and taxpayer ethics education to reduce state losses due to tax fraud. This study contributes to the tax literature with an integrative model that combines corporate fraud theory and morality aspects, and suggests longitudinal empirical research for further validation in the Indonesian context.